2015
DOI: 10.1177/1756285615615257
|View full text |Cite
|
Sign up to set email alerts
|

Exploring potential mechanisms of action of natalizumab in secondary progressive multiple sclerosis

Abstract: Multiple sclerosis (MS) is a common and chronic central nervous system (CNS) demyelinating disease and a leading cause of permanent disability. Patients most often present with a relapsing-remitting disease course, typically progressing over time to a phase of relentless advancement in secondary progressive MS (SPMS), for which approved disease-modifying therapies are limited. In this review, we summarize the pathophysiological mechanisms involved in the development of SPMS and the rationale and clinical poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 105 publications
1
29
0
Order By: Relevance
“…Because natalizumab inhibits trafficking of lymphocytes from the blood into the CNS, its clinical benefit can be postulated in secondary progressive MS, in which CNScompartmentalized inflammatory processes may predominate (24). Also, previous studies suggested evidence of improved tissue integrity and enhanced axonal metabolism in some natalizumab-treated RRMS patients (25,26).…”
Section: Pivotal Phase III Trialsmentioning
confidence: 99%
“…Because natalizumab inhibits trafficking of lymphocytes from the blood into the CNS, its clinical benefit can be postulated in secondary progressive MS, in which CNScompartmentalized inflammatory processes may predominate (24). Also, previous studies suggested evidence of improved tissue integrity and enhanced axonal metabolism in some natalizumab-treated RRMS patients (25,26).…”
Section: Pivotal Phase III Trialsmentioning
confidence: 99%
“…Treatments for relapsing multiple sclerosis generally act on the peripheral immune response. 14 Their limited effects on progressive disability suggest that the mechanisms of tissue injury are diverse in progressive multiple sclerosis. Particular interest has emerged in the intrathecal immune response, which is shielded from peripherally acting agents behind the blood-brain barrier.…”
Section: Introductionmentioning
confidence: 99%
“…Particular interest has emerged in the intrathecal immune response, which is shielded from peripherally acting agents behind the blood-brain barrier. 14 Natalizumab, a recombinant humanised monoclonal antibody against α4 integrin (very late antigen4), is highly effective in relapsingremitting multiple sclerosis 15 and appears to suppress intrathecal inflammation. 14 Natalizumab inhibits leucocyte transmigration across the blood-brain barrier, interferes with chemokinemediated inflammatorycell recruitment into the CNS, and disrupts the production of molecules required to sustain intrathecal inflammation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations